2016
DOI: 10.1590/1678-4766e2016024
|View full text |Cite|
|
Sign up to set email alerts
|

Three new species of Leptohyphes Eaton (Ephemeroptera: Leptohyphidae) from Colombia

Abstract: ABSTRACT. Three new species of Leptohyphes Eaton, 1882 (Ephemerotera: Leptohyphidae) are described, diagnosed and illustrated from nymphs collected in Colombia. Geographical ranges and ecological notes relating important environmental variables are given for each species. Leptohyphes andina sp. nov. is characterized by: forefemur length / maximum width 1.8-1.9, fore and hind margin of middle and hind femora with strong spine-like setae on elevated sockets, femoral surface covered by small pale spots, apex of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In relation to upper limits of mayfly genera, Crespo‐Pérez et al. () and Molineri, Zúñiga, Ramos, Giraldo, and Cardona () found that Leptohyphes reaches 3,000 to 3,300 m in Ecuador and Colombia, respectively, in broad concordance with CBL prediction for a typical taxon from the warm group. Crespo‐Pérez et al.…”
Section: Discussionmentioning
confidence: 72%
“…In relation to upper limits of mayfly genera, Crespo‐Pérez et al. () and Molineri, Zúñiga, Ramos, Giraldo, and Cardona () found that Leptohyphes reaches 3,000 to 3,300 m in Ecuador and Colombia, respectively, in broad concordance with CBL prediction for a typical taxon from the warm group. Crespo‐Pérez et al.…”
Section: Discussionmentioning
confidence: 72%